Effectiveness of wellness program interventions to improve physician wellness: a systematic review - Kolobaric, Nikola; Milone, Benjamin; Salman, Maria; Buh, Amos; Biyani, Nandini; Wafy, Gamal; Fung, Stephen G.; Scott, Mekaylah; Kiska, Rohan; Kang, Rachel; Lee, Kathryn; Syed, Sarah; et al. (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Physician wellness programs are being implemented to offset rises in physician burnout. Insight into the effectiveness of these programs and to whom they are being offered, remains unclear. Objectives To identify and characterize wellness program interventions to improve physician wellness. Methods A PRISMA-P 2020-compliant systematic review as conducted, searching PubMed, Scopus, and Medline from May 2006 to July 2024. Search terms included Medical Subject Headings terms and keywords related to physicians and wellness program interventions. Peer reviewed published studies that qualitatively and/or quantitively measured outcomes of wellness interventions for practicing physicians were included. Results Thirty-six studies involving 6,708 total participants were included. Interventions were heterogenous and included group therapy, stress reduction strategies, time off/workload reductions, education, and peer support. The efficacy of interventions varied, with sixteen studies (44.4%) demonstrating some measurable degree of effectiveness, with statistically significant changes (p < 0.05) post-intervention. Few studies reported improvements by physician sex, age groups, or comparisons across specialities. Conclusion Studies examining physician wellness program interventions are highly heterogenous in terms of intervention, study design and methods of outcome assessment, limiting definitive conclusions about their general effectiveness. Trial registration The review protocol has been registered on Open Science Framework ( https://doi.org/10.17605/OSF.IO/8SDM9 ).